Investigating secondary school learners' academic achievement in physics in Uganda - Lugolole Robert; Ntongo Dorothy; Marjorie S K Batiibwe; Sentongo John; Kibirige Israel (Ömer Gökhan Ulum, 2024)
This study examined secondary school learners' academic achievement in physics in the Wakiso district of Uganda. A cross-sectional correlational design was used with 217 participants. This comprised 121 male and 96 female learners from two government-aided secondary schools in Kira Municipality, Wakiso district. Data were collected using a Self-Administered Questionnaire (SAQ) and analysed using descriptive statistics such as percentages and mean scores. Analysis of Variance (ANOVA) and Pearson's linear correlation coefficient were applied for inferential statistics. The results show a positive relationship between learners' aptitude, learning environment, and academic achievement, while a negative relationship was between teachers' instruction and academic achievement in physics. These results have far-reaching implications for improving academic achievements in physics. The study recommended investing in a more friendly learning environment by upskilling in-service teachers through professional development programs to enhance their pedagogy and conduct parent meetings to sensitise them to create a conducive home learning environment.